Nurses’ Perceptions on the Usability of Electronic Health Records: A Scoping Review - Moore, Sarah Jane; Garnett, Anna; Mason, Kelly; Onigbinde, Eunice; Yurkiv, Halyna (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2025)
Introduction: Electronic health records (EHRs) are designed to enhance the efficiency and quality of nursing workflows and documentation. EHR usability refers to how effectively the system supports users to accomplish their work tasks. However, the understanding of nurses’ perceptions of EHRs usability in inpatient settings is limited. Objective: Examine the available literature on nurses’ perceptions of EHRs usability in these settings. Methods: This scoping review was guided by the Arksey and O’Malley (2005) methodology and methodological steps of the Joana Brigs Institute (Peters et al., 2015). Search terms included combinations of synonyms for nurses, perceptions, and EHRs usability. Eligible sources of data were primary research studies published in English between January 1, 2013, and July 1, 2024, and extracted from PubMed, CINAHL, and Scopus databases. Inclusion criteria targeted Registered Nurses and Registered Practical Nurses in inpatient hospital settings in North America, Europe and Australia. Findings were presented descriptively and thematically using a narrative analysis. Results: Twenty studies met the inclusion criteria. The narrative synthesis generated five themes: 1) ease of information accessibility; 2) nursing workflow challenges; 3) EHR design, technical issues, interoperability; 4) impact of the EHR on the nurse-patient relationship, and 5) user training. Nurses identified factors that positively impacted EHRs usability, such as real-time access to patient information in one location, the ability to view patterns and trends in patient status, and improved interprofessional collaboration, but they shared disproportionally negative perceptions of EHRs usability. Discussion and Conclusion: Future research should focus on addressing these challenges to optimize EHR design, enhance training strategies, and improve system interoperability, ultimately supporting nursing workflows and enhancing patient care quality.